Credit Portfolio Management in Financial Institutions - Sawhney, Mamta (2005)
The past few years have seen tremendous markets dynamics. There is an unprecedented growth in market and at the same time there is development of newer and complicated financial products. Times are of grand scale transactions and thus grand credit requirements. This has caught the fancy of the regulators as well as financial institutions that are increasingly being aware of sound credit risk management strategies. However, the approach is changing its face.